PENGARUH PENYULUHAN MENGGUNAKAN MEDIA BONEKA TANGAN TERHADAP RETENSI PENGETAHUAN MENYIKAT GIGI PADA ANAK USIA 6-8 TAHUN DI MIN 14 BANJAR MARTAPURA - Gusti Aprilisa Nurhuda; Waljuni Astu Rahman; Fahmi Said (Poltekkes Kemenkes Banjarmasin, 2021)
Abstract: The proportion of people's behavior over 3 years old in brushing their teeth every day is 96% but 4-5.6% are doing dental behavior at the right time. One of the efforts to improve health (promotive) is counseling. Of the 10 children sampled for the preliminary study, it was found that 3 children had good knowledge, 3 children had moderate knowledge, and 4 children had less knowledge about teeth. This study aims to determine the effect of media use counseling on the development of dental knowledge in children aged 6-8 years at MIN 14 Banjar Martapura. This type of research is analytical research. This research design is a quasi-experimental. This research is a pretest-posttest design. The sampling technique used was purposive sampling with a population of 141 children with a sample of 63 children. The result of dental knowledge research is 6.22 pretest and posttest 1 is 7.46. Knowledge retention is 7, posttest 1 is 7, and posttest 2 is 7,36. Test the effect using Wilcoxon with a value of p = 0.000 and a value of a = 0.05 which means p <a. The conclusion of this study is that there is an effect of counseling using hand puppet media on the retention of dental knowledge in children aged 6-8 years at MIN 14 Banjar Martapura. Suggestions for conducting counseling, for further researchers need to add other media as a comparison of media that may also affect the development of teeth. Keywords: Knowledge Retention-Hand Puppet